2014
DOI: 10.1177/1365480214556419
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming stereotypes, discovering hidden capitals

Abstract: This article presents a model of teacher research supported by academic partners to develop a better understanding of the barriers to education faced by young people growing up in poverty. It critiques politicians' demands for teachers to 'close the gap' for ignoring the cumulative intergenerational effects of deprivation. The authors explain how a simplistic 'craft' version of teaching has tended to reduce initial teacher education in England to training in the pragmatics of curriculum 'delivery' and policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Humans are complex beings. Our social standing is dependent upon complex interrelated factors, such as gender, race, ethnicity (Beckett & Wrigley, 2014;Dunne & Gazeley, 2008;Glock et al, 2014;Parks & Kennedy, 2007;Peterson et al, 2016), social status, wealth (Dunne & Gazeley, 2008;Peterson et al, 2016), sexual orientation, and educational attainment (Hughes, Gleason, & Zhang, 2005), all of which influence structural, cultural, and social identities, which are intertwined with material and power inequities. Inequities can surface with individual or group identity evaluation, coupled with actions that may privilege or obstruct resource access (O'Connor, 2001).…”
Section: Cultural Capital Theory Rationalementioning
confidence: 99%
See 4 more Smart Citations
“…Humans are complex beings. Our social standing is dependent upon complex interrelated factors, such as gender, race, ethnicity (Beckett & Wrigley, 2014;Dunne & Gazeley, 2008;Glock et al, 2014;Parks & Kennedy, 2007;Peterson et al, 2016), social status, wealth (Dunne & Gazeley, 2008;Peterson et al, 2016), sexual orientation, and educational attainment (Hughes, Gleason, & Zhang, 2005), all of which influence structural, cultural, and social identities, which are intertwined with material and power inequities. Inequities can surface with individual or group identity evaluation, coupled with actions that may privilege or obstruct resource access (O'Connor, 2001).…”
Section: Cultural Capital Theory Rationalementioning
confidence: 99%
“…Educators could support and assist students in meeting their expectations through positive reinforcement (Termes . But research has demonstrated that teacher interactions with students varies depending on the child, context, and often, social categories (Beckett & Wrigley, 2014;Pringle et al, 2010;Termes Lopez, 2017). Even though stigmatized groups were found to be more susceptible to lower performance due to underestimations of ability (de Boer et al, 2010), children have been found to be resilient, capable of developing strategies to compensate for unequal treatment (Termes .…”
Section: Effects and Teacher Expectation Biasmentioning
confidence: 99%
See 3 more Smart Citations